Improving Anxiety Related to Chronic Pain Through a Sleep Circadian Intervention Program: A Pilot Study - Sonia López-Monzoni; Gloria Hernando Benito; Sofía Romero-Peralta; Laura Silgado-Martínez; Maria Esther Viejo-Ayuso; Leticia Álvarez-Balado; Enrique Rodríguez Matarranz; Carles Forné Izquierdo; Manuel Sánchez-de-la-Torre; Juan Fernando Masa; Ferrán Barbé; Francisco García-Río; et al. (Behavioral Sciences)
The limitations of pharmacological treatments for chronic pain have become increasingly evident: dependency, side effects, resistance, and diminishing efficacy. The urgent need for innovative solutions has become a compelling focus for improving patient outcomes. Innovative non-pharmacological approaches, such as sleep management, as a strategy to reduce opioid consumption and pain control are needed. The aim was to evaluate the impact of a Sleep and Circadian Intervention Program (SCIP) in the control of chronic musculoskeletal pain (CMP). This was a randomized clinical trial (NCT03646084), in which 49 CMP patients were assigned to SCIP (n = 15, mean age 51 years and 40% women) or non-SCIP groups (n = 26, 53 years and 61.5% women). Outcomes were evaluated after 6 months through self-reported questionnaires (pain intensity, physical function, depression/anxiety, and quality of life (QoL)). The SCIP group was assessed by polysomnography and specific questionnaires and was treated for diagnosed sleep disorders according to clinical guidelines. This population showed a moderate pain intensity at baseline, important deterioration of QoL and pathological anxiety/fear related to pain. Fifty percent of them presented restless leg syndrome, 60% moderate/severe insomnia, and 62.5% sleep apnea. During the follow-up, the SCIP group presented a greater reduction in the abnormal risk group for anxiety (from 73.3% to 46.7%) and depression (from 53.3% to 33.3%) on the Hospital Anxiety and Depression Scale compared to the non-SCIP group (from 40% to 29.2% and 33.3% to 29.2%, respectively). Also, a positive significant effect on anxiety/fear related to pain was found in the Pain Anxiety Symptoms Scale multivariable model, with an important improvement in symptoms. The application of SCIP in CMP patients improved anxiety and controlled associated sleep disorders, highlighting the impact on insomnia. Larger studies are needed for better understanding of the sleep intervention in CMP control.